Analysis and exact solutions for reaction–diffusion predator–prey system with prey-taxis by phi6 method - Rishi Naeem; Muhammad Sajid Iqbal; Ali Hasan Ali; Mustafa Inc (Nonlinear Analysis)
This article analyses the biomathematical model that describes the reaction–diffusion predator–prey system with prey-taxis. The analysis includes addressing the question of whether the solution exists and is unique. The next goal is to obtain the exact solutions. The ɸ6 method has been utilized for this purpose. The simulations of the obtained solutions are also incorporated, providing a broader understanding of the solutions.